2017
DOI: 10.1186/s12889-017-4704-y
|View full text |Cite
|
Sign up to set email alerts
|

Asthma hospitalisation trends from 2010 to 2015: variation among rural and metropolitan Australians

Abstract: BackgroundAsthma remains a leading cause of illness, where primary care can assist to reduce hospitalisations through prevention, controlling acute episodes, and overall management of asthma. In Victoria, Asthma hospitalisations were as high as 3.1 hospitalisations per 1000 population in 1993–94. The primary aims of this study are to: determine if changes in asthma hospitalisations have occurred between 2010 and 2015; determine the key factors that impact asthma hospitalisation over time; and verify whether ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…This finding is consistent with previous studies carried out in Denmark and Sweden which showed that breastfeeding does not lower the risk of childhood asthma (OR: 1.08, 95% CI: 0.93-1.25) and (OR: 0.99, 95% CI: 0.96-1.02) respectively [47,48] Mode of delivery, gender, maternal and household smoking as well as maternal asthma are potential risk factors for asthma in children as demonstrated by several studies [49][50][51][52][53][54]. Gender appears to be a factor in the development of asthma, where boys in general are reported to have more severe asthma than girls [50] and higher rates of admission to hospitals [52,55]. Researchers have attributed this to airway hyper-responsiveness in childhood that is more common and more severe among males than females.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with previous studies carried out in Denmark and Sweden which showed that breastfeeding does not lower the risk of childhood asthma (OR: 1.08, 95% CI: 0.93-1.25) and (OR: 0.99, 95% CI: 0.96-1.02) respectively [47,48] Mode of delivery, gender, maternal and household smoking as well as maternal asthma are potential risk factors for asthma in children as demonstrated by several studies [49][50][51][52][53][54]. Gender appears to be a factor in the development of asthma, where boys in general are reported to have more severe asthma than girls [50] and higher rates of admission to hospitals [52,55]. Researchers have attributed this to airway hyper-responsiveness in childhood that is more common and more severe among males than females.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the Accessibility and Remoteness Index of Australia 2011 (ARIA+) was also used. The ARIA+ measures the level of geographical remoteness of LGA by examining the road distance to goods and services with respect to population size; the key data sources outlined provided the specific LGA measures required for data analysis . The mean ARIA+ scores were used for each individual LGA and were scored as ‘highly accessible’ (0–0.2), ‘accessible’ (0.2–2.4) and ‘moderately accessible’ (2.4–5.92) …”
Section: Methodsmentioning
confidence: 99%
“…Hospitalisation data for a five-year period from July 1, 2010 to June 30, 2015 were obtained from the Victorian Admitted Episodes Dataset (VAED). As discussed elsewhere, 16 data included sex, age (five-year age groups), LGA or region of residence, private or public patient, bed days used as the unit of measurement for length of stay, type of discharge and diagnosis on hospitalisation according the ICD-10-AM. COPD as the principal diagnosis was identified using the ICD-10-AM codes J43.1, J43.2, J43.8, J43.9, J44.0, J44.1, J44.8 and J44.9.…”
Section: Data Collectionmentioning
confidence: 99%
“…Ethical approval for the research was obtained in March 2015. Others sources of data were included as outlined previously, 16 and were sourced from the Australian Bureau of Statistics. 17…”
Section: Data Collectionmentioning
confidence: 99%